Small Prey Animal Foraging Behaviors in Landscapes of Fear: Effects of Predator Presence and Human Activity Along an Urban Disturbance Gradient - Fardell, Loren L.; Nano, Catherine E. M.; Pavey, Chris R.; Dickman, Christopher R. (Frontiers in Ecology and Evolution, 2022)
Urban environments provide the only or best habitats that are left for wildlife in many areas, promoting increased interest in urban conservation and a need to understand how wildlife cope with urban stressors, such as altered predator activity and human disturbance. Here, we used filmed giving-up density experiments to investigate behavioural coping responses of foraging small prey animals at three sites (close, mid, and far) along an urban disturbance gradient. Our study design included ‘natural’ and experimentally added stressor cues of predators and/or human disturbance. We observed small mammal foraging behaviours, particularly: the common brushtail possum (Trichosurus vulpecula), northern brown bandicoot (Isoodon macrourus), brown antechinus (Antechinus stuartii), black rat (Rattus rattus), and brown rat (Rattus norvegicus), and to a lesser degree several species of native birds. We found that at the close urban-edge environment, coping responses to human disturbances were most pronounced, and predator cues from the red fox (Vulpes vulpes) were perceived as least risky. However, at the mid environment, red fox cues were perceived as most risky, especially when combined with human disturbance. At the far environment, domestic cat (Felis catus) cues were perceived as most risky, again when combined with human disturbance. Impacts from the combined stressors of predator and human disturbance cues appeared to be additive, with higher risk being perceived with increasing distance from urban build-up. Behavioural adjustments were observed to be the primary response to stressors by small prey animals in the close environment. In the mid environment, slight temporal shifts in activity across the night were more evident. In the far environment, habitat components were likely being used differently as the primary coping response to stressors. As mostly the same species were observed along the disturbance gradient, our results suggest a level of response plasticity that is calibrated to the level of exposure to a stressor and the stressor type. To maximise conservation outcomes in urban habitats, we therefore propose that management should be sensitive to the level and history of human disturbance, as this affects the coping responses of wildlife that remain.